Interpreting the Dæmonomicon: A Decade of Teaching Philip Pullman's Northern Lights - Jessica Allen Hanssen (CLELEjournal, 2018)
Philip Pullman's His Dark Materials trilogy reinvigorated the high fantasy genre, not least by his invention of the dæmon. In this article I argue that the dæmon concept, when applied as a drawing exercise in the teacher education context, provides important insight into the vast diversity of interests, feelings, and values of ELT student teachers as they prepare to enter their chosen profession. From the years 2007-2017, approximately 200 university students were invited to draw a representation of their 'dæmon'. The drawings, assembled and analysed as a data set based on markers such as the student teachers' gender, as well as by content, size, and relative creativity, allow certain patterns and tendencies to become visible, and individual drawings also serve as important reflection points on the novel and the nature of teaching literature. Northern Lights, the first book of His Dark Materials trilogy, makes for excellent reading, and is also a helpful book to use in the teacher education context, to help student teachers learn the conventions of the fantasy genre and understand how knowledge of the genre can enhance their teaching practice. This article therefore presents a long-term learning activity connected to teaching Northern Lights, as a way into working with genre conventions, and also as a point of departure on the subject of the importance of self-reflection in the literature classroom's interpretative community.